Chloroplast dedifferentiation in mechanically isolated asparagus cells during culture initiation - Harikrishna, Kulaveerasingham; Darby, Robert; Draper, John (American Society of Plant Biologists, 1992)

(untitled)
Mechanically isolated asparagus (Asparagus officinalis) mesophyll cells dedifferentiate and divide when cultured in the dark in a medium containing sucrose. A strong correlation was observed between the onset of cell division and a loss of photosynthetic capacity. For the first 8 to 9 d of culture, there was no change in chloroplast size or morphology. However, following this period, the chloroplasts divided to form smaller proplastid-like structures. The gross chlorophyll content of the cell population did not change, suggesting that the loss of photosynthetic potential was not by senescence. Northern analysis showed that mRNA of the small subunit of ribulose l,5-bisphosphate carboxylase/OJeygenase was undetectable within 1 d postisolation, which was quicker than in dark-treated plants. The mRNA of the large subunit of ribulose 1,S-bisphosphate carboxylase/oxygenase decreased to low levels within 2 d of cell isolation. Both the large and small subunits of ribulose l,S-bisphosphate carboxylase/oxygenase protein showed a gradual reduction in abundance, falling to basal levels by days 6 to 7, which coincided with the onset of rapid cell division. A similar trend was observed with chloroplast rRNA molecules, which decreased to basal levels by day 6 in culture